Analog and Mixed-Signal IC Security via Sizing Camouflaging - Leonhard, Julian; Sayed, Alhassan; Louerat, Marie-Minerve; Aboushady, Hassan; Stratigopoulos, Haralampos-G. (IEEE transactions on computer-aided design of integrated circuits and systems, 2021)
We treat the problem of analog integrated circuit (IC) obfuscation toward intellectual property (IP) protection against reverse engineering. Obfuscation is achieved by camouflaging the effective geometry of layout components via the use of fake contacts, which originally were proposed for gate camouflaging in digital ICs. We present a library of obfuscated layout components, we give recommendations for effective camouflaging, we discuss foreseen attacks and the achieved resiliency, and we propose security metrics for assessing the hardness of reverse engineering. The proposed methodology is demonstrated on an operational amplifier and an RF Σ Δ analog-to-digital converter (ADC).